The Effect of Inactivated Mycobacterium Paratuberculosis Vaccine on the Response to a Heterologous Bacterial Challenge in Pigs - Jensen, Kristoffer Jarlov; Hansen, Mette Sif; Heegaard, Peter Mikael Helweg; Benn, Christine Stabell; Jungersen, Gregers (Frontiers in Immunology, 2019)
Background: Vaccines may have non-specific effects, affecting resistance to heterologous pathogens. Veterinary vaccines have seldom been investigated for their non-specific effects. However, recent observational studies suggest that an inactivated paratuberculosis vaccine reduced all-cause mortality in goats and cattle. Aim: We tested if vaccination with a killed mycobacterial vaccine may have heterologous effects in swine (Sus domesticus), specifically on the pathogenic and clinical effects of a heterologous challenge with Actinobacillus pleuropneumoniae in young pigs. Methods: Newborn piglets were randomized to vaccination s.c. with the inactivated paratuberculosis vaccine Gudair (Zoetis Inc.) (n=17) or no vaccine (n=16). At 4-5 weeks after vaccination, all piglets were challenged intra-nasally with a high (Gudair: n=8; control: n=8) or a low (Gudair: n=9; control: n=8) dose of the gram-negative bacterium A. pleuropneumoniae causing acute porcine pleuropneumonia. The effect and severity of pathogen challenge was evaluated by measuring acute phase proteins C-reactive protein, haptoglobin and Porcine α1-acid glycoprotein, and by gross pathology one day post challenge. Specific and non-specific in vitro cytokine responses to vaccination were evaluated in whole blood before bacterial challenge. Results: The vaccine was immunogenic in the pigs as evidenced by increased IFN-γ responses to purified protein derivative of Mycobacterium paratuberculosis. However, Gudair vaccine did not affect IL-6 responses. The gross pathology of the lungs as well as the acute phase protein responses after the high A. pleuropneumoniae dose challenge was slightly increased in the vaccinated animals compared with controls, whereas this was not seen in the animals receiving the low-dose bacterial challenge. Conclusion: The inactivated paratuberculosis vaccine exacerbated the pathological and inflammatory effects of an experimental A. pleuropneumoniae infection in young pigs.